Optimized Ultrawideband and Uniplanar Minkowski Fractal Branch Line Coupler - Mohammad Jahanbakht; Mohammad Tondro Aghmyoni (International Journal of Antennas and Propagation)
The non-Euclidean Minkowski fractal geometry is used in design, optimization, and fabrication of an ultrawideband (UWB) branch line coupler. Self-similarities of the fractal geometries make them act like an infinite length in a finite area. This property creates a smaller design with broader bandwidth. The designed 3 dB microstrip coupler has a single layer and uniplanar platform with quite easy fabrication process. This optimized 180° coupler also shows a perfect isolation and insertion loss over the UWB frequency range of 3.1–10.6 GHz.